MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK SMP MELALUI STRATEGI KONFLIK KOGNITIF PENDEKATAN PROBLEM-BASED LEARNING (PBL) DENGAN SIKAP PESERTA DIDIK SEBAGAI VARIABEL INTERVENING - Nandang Arif Saefuloh; Bana Goerbana Kartasasmita; Usep Kosasih (Universitas Islam Nusantara, 2020)
Contextual mathematical questions make it difficult for students to solve, however, the problem is needed to train students' cognitivelevels, furthermore, in contextual matters, students are required to have problem-solving abilities, which are the focus of mathematicslearning by many experts. mathematics education. The design of this study is a mixed method with the Concurrent Embedded Model.The population of this study was all students of XYZ Junior High School Bandung with a sample of class VII students as many astwo classes selected purposively. Data analysis was carried out quantitatively and qualitatively. Quantitative analysis was performedon the initial test data, the final test, and the normalized gain of mathematical problem solving abilities, as well as on the test data ofthe two groups performed a mean difference test between the two populations and two-way ANOVA. Qualitative analysis wasconducted to examine students' attitudes toward learning using cognitive conflict strategies with the PBL approach. The results showedthat increasing the problem solving ability of students who get learning by using the cognitive conflict strategy PBL approach is betterthan students who get conventional learning as measured by the MEA of students, as well as, student attitudes as positive interveningvariables towards learning with conflict learning cognitive PBL approach.